2022
DOI: 10.3390/app12094121
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Antioxidant, Antifungal, and Wound Healing Activities of Solenostemma arghel Ethyl Acetate and Methanolic Extracts

Abstract: Various herbal compounds are used for medical purposes due to their safety, as there are no or minimal side effects. This study was performed to assess the wound healing and antioxidant activities of ethyl acetate (EtOAc) and methanolic extract (MeoH) of Solenostemma arghel (S. arghel). Their antifungal activities were also evaluated against isolated swabs of equine wounds. They underwent GC-MS analysis for the characterization of both extracts. For wound healing evaluation, forty-five male albino rats were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Many researchers believe that VEGF promotes wound epithelialization and collagen deposition so that high levels of VEGF are produced during the normal wound repair (Chereddy et al 2015 ). ODHP-NS-HG–treated group (E) exhibited significantly ( p < 0.05) higher level of VEGF compared to the infected untreated group (B) denoting increased level of re-epithelization and collagen deposition in accordance with previous studies (Abdel-Motaal et al 2022 ). Cyclooxygenases are essential enzymes in the production of prostaglandins (PGs) from arachidonic acid.…”
Section: Discussionsupporting
confidence: 90%
“…Many researchers believe that VEGF promotes wound epithelialization and collagen deposition so that high levels of VEGF are produced during the normal wound repair (Chereddy et al 2015 ). ODHP-NS-HG–treated group (E) exhibited significantly ( p < 0.05) higher level of VEGF compared to the infected untreated group (B) denoting increased level of re-epithelization and collagen deposition in accordance with previous studies (Abdel-Motaal et al 2022 ). Cyclooxygenases are essential enzymes in the production of prostaglandins (PGs) from arachidonic acid.…”
Section: Discussionsupporting
confidence: 90%
“…Also, the potent antimicrobial activity of PsEAE prevents wound infection. Several reports showed different endophytic fungi extracts' extraordinary wound healing properties 72 , 73 . Recent study has shown a remarkable wound healing properties of natural extracts of Rosmarinus officinalis L. to emphasize the importance of discovering novel and safe bioactive compounds from natural sources 74 .…”
Section: Resultsmentioning
confidence: 99%
“…As a result, infection is a major wound complication, and antibacterial medicines are vital in the wound-healing process. 26 , 48 …”
Section: Discussionmentioning
confidence: 99%